IMPLEMENTASI KEBIJAKAN PERATURAN DAERAH KOTA SEMARANG NOMOR 5 TAHUN 2010 TENTANG PENGENDALIAN PENYAKIT DEMAM BERDARAH DENGUE (DBD) DI KECAMATAN TEMBALANG (PUSKESMAS KEDUNGMUNDU) - Lestari, Elyzabeth; Suryaningsih, Margaretha (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2019)
The Dengue Hemorrhagic Fever (DHF) Control is an activity that consists of prevention and handling activities to break the chain of the dengue transmission. DHF is one of the endemic diseases in the city of Semarang, and Tembalang district is a sub-district that has the highest number of DHF patients every year. Based on this phenomenon, the Semarang City Government issued a Regional Policy Numb. 5 Year 2010 concerning the Control of DHF. The purpose of this study are to describe how the implementation of Regional Policy Numb. 5 Year 2010 concerning the Control of DHF in Tembalang District, Semarang City is and to find out the inhibiting factors of Regional Policy Numb. 5 Year 2010 concerning the Control of DHF in Tembalang District, Semarang City. This research is a type of descriptive research using descriptive qualitative method. Data collection techniques that are used consist of interview and documentation. Data analysis is implemented by collecting the data, data reduction, data explanation, and conclusion. The result of the study shows that this policy has been implemented since 2010, and the number of DHF sufferers is getting decreased. However, its implementation still encounters various obstacles, such as inadequate resources, poor quality of communication, lack of compliance with the policy content, and so on. Several recommendations regarding those problems can be given by applying some solution such as adding the number of officers, improving the intensity and quality of information delivery about the Regional Policy, evaluating the standard of operating procedures (SOP), and strengthening the coordination and cooperation between the implementing parties and other parties.